2011
DOI: 10.1159/000328199
|View full text |Cite
|
Sign up to set email alerts
|

Unusually Long Survival of a 67-Year-Old Patient with Near-Tetraploid Acute Myeloid Leukemia M0 without Erythroblastic and Megakaryocytic Dysplasia

Abstract: Patients with near-tetraploid acute myeloid leukemia (NT-AML) typically have poor survival. We present the case of a 67-year-old Caucasian male with NT-AML M0 who had an unusually long first complete remission of 51 months and an overall survival of 80 months. The only characteristic distinguishing him from other previously described patients with NT-AML was the absence of erythroblastic and/or megakaryocytic dysplasia (EMD) at diagnosis. Molecular-genetic testing for AML fusion transcripts associated with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Moreover, the patient was a young man with good underlying conditions so possibly these issues are an important point in the long survival of our patient. In the literature, there are also other near-tetraploidy or tetraploidy AML reported cases with unusually long survival 10. In this case report for example, the authors highlight the absence of dysplasia at diagnosis as the main reason of a better overall survival.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the patient was a young man with good underlying conditions so possibly these issues are an important point in the long survival of our patient. In the literature, there are also other near-tetraploidy or tetraploidy AML reported cases with unusually long survival 10. In this case report for example, the authors highlight the absence of dysplasia at diagnosis as the main reason of a better overall survival.…”
Section: Discussionmentioning
confidence: 65%
“…Although the patient received only one course of remission induction chemotherapy due to severe comorbidities, he remained in complete remission for more than 40 months without any consolidation or maintenance therapies. Lemez et al also reported a case of NT-AML with unusually long survival (80 months) (9). Some cases of NT/T-AML might have a better prognosis than generally expected.…”
Section: Discussionmentioning
confidence: 88%
“…Two further cases of patients over 65 years old enlarge our knowledge of a good sensitivity of GM-AML to SICT. A 67-year old man with de novo Near-Tetraploid (NT) GM-AML M0 with WBC 52.9×10 9 /L reached CR and survived 51 months in CR after three 3+7 cycles [24] while most European cases with de novo NT-AML were EMD-AML with 33 % CR rate and maximal survival 31.5 months after SICT [30]. In 2017-8 we treated an 86-year old man diagnosed with GM-AML, normal karyotype with NPM1 mutation and FLT3-ITD, WBC 33.7×10 9 /L in 2011, who reached CR after two cycles of These two cases of patients over 65 years with GM-AML and all of our 6 octogenarian cases treated with SICT had WBC over 15×10 9 /L, the threshold over which treatment with Hypomethylating Agents (HMA) azacytidine or decitabine has not been recommended [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The French-American-British (FAB) classification [23] with standard cytochemical and immunophenotyping methods was used for establishing the diagnosis of AML [23,17]. Cytogenetic and I-FISH analyses were made from 24-hour unstimulated cultures of patients' bone marrow cells at diagnosis [17,24]. Molecular-genetic analyses were performed on cDNA obtained by reverse transcription of RNA (or for CEBPA from genomic DNA by sequencing the multiplied entire coding region of CEBPA) from bone marrow mononuclear cells at diagnosis as reported [24].…”
Section: Study Groupmentioning
confidence: 99%
See 1 more Smart Citation